DIRECTIVE SPEECH ACTS USED IN “STRANGER THINGS: SEASON 2” SERIAL MOVIE BY THE DUFFER BROTHERS - Sari, Rossa Tirta; Mubarak, Zia Hisni (SCIENTIA JOURNAL, 2020)
This research describes about pragmatics in the specific domain of directive speech acts found in Stranger Things: season 2. The aim of this research is to find out the type of directive speech acts based on Ibrahim's theory in one of the series films. In this research researchers used qualitative methods. Data is collected based on utterances contained in the series of films using observation methods and non-participatory techniques. Researchers use identity methods in analyzing data. The research found several types of directive speech acts. There are 35 data types of directive speech acts consist of requestive (7 data), question (11 data), requirements (9 data), prohibitive (2 data), permissive (1 data), and advisories (5 data). In the data types of data found there are different purposes. The findings of this study indicate that the data most frequently found in types of directive speech are questions.